Economia, entropia e sustentabilidade: abordagem e visões de futuro da Economia da sobrevivência - Mueller, Charles C. (Estudos Econômicos (São Paulo), 1999)
The paper evaluates theeconomics of survival - o school of thought that emphasizes thepreservation of the opportunities of future generations on an extended time horizon. Itexamines the school's approach on the interactions between the economic system andthe environment, and its main analytical concepts, particularly that of entropy. It showsthat the concern of the school's founders was mainly with the consequences of a seriousdepletion of natural resources - particularly those of the earth's energy capital. Recently,however, emphasis was placed on problems stemming from the fragility of the globalsystem in face of growing disturbances imposed by mankind's entropic acceleration.There are vital environmental functions, especially the preservation of ecosystem resiliency,and it is argued that a continued expansion of the scale of the economy may bring aboutirreversible damages to these fundamental functions.